Pengaruh Supervisi Akademik, Disiplin Guru dan Budaya Kerja terhadap Kinerja Guru SD Negeri di Wilayah Pedurungan - Setyawati, Ariani Nur; Kusumaningsih, Widya; Sulianto, Joko (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Good teacher performance is needed in managing learning so that learning objectives can be achieved perfectly. The aim of the research is to analyze the influence of academic supervision, teacher discipline and work culture on teacher performance. This type of research is correlational. The research sample consisted of 189 teachers. Data was collected using questionnaire techniques. Based on the research results, it is known that: 1) the correlation between supervision and teacher performance is 0.993. The effect of supervision on teacher performance is 98.6%, 2) the correlation between discipline and teacher performance is 0.893. The influence of discipline on teacher performance is 79.8%, 3) the correlation between work culture and teacher performance is 0.910. The influence of work culture on teacher performance is 82.9%, 4) the correlation between academic supervision, teacher discipline and work culture and teacher performance is 0.994. The influence of academic supervision, teacher discipline and work culture on teacher performance is 98.9%. Thus, the conclusion of this research is that academic supervision, teacher discipline and work culture on teacher performance is 0.994 or 98.9%.